2019
DOI: 10.1111/opo.12655
|View full text |Cite
|
Sign up to set email alerts
|

To rub or not to rub? – effective rigid contact lens cleaning

Abstract: Purpose To compare the efficacy of cleaning of rigid contact lenses using two care solutions with and without rubbing. Methods A masked randomised trial was conducted. The cleaning efficacy of two solutions recommended for rigid contact lenses, a one‐step hydrogen peroxide solution (HP) and a povidone iodine‐based solution (PI), were evaluated on 64 unworn orthokeratology (ortho‐k) lenses subsequent to cleaning with rubbing (R) with a surfactant cleaner or without rubbing (NR). Either mascara or hand cream was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Despite the availability of many MPDS for use with either reusable soft or rigid corneal lenses being approved as 'no-rub' care regimens, studies demonstrate the additional benefit of rubbing lenses [332,381,382]. Furthermore, good lens hygiene and compliance, including proper cleaning and disinfection and maintenance of cases for lens storage, and diligence with wearing and replacement schedules, are essential in minimizing the risk of ocular complications [262,263,276].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the availability of many MPDS for use with either reusable soft or rigid corneal lenses being approved as 'no-rub' care regimens, studies demonstrate the additional benefit of rubbing lenses [332,381,382]. Furthermore, good lens hygiene and compliance, including proper cleaning and disinfection and maintenance of cases for lens storage, and diligence with wearing and replacement schedules, are essential in minimizing the risk of ocular complications [262,263,276].…”
Section: Discussionmentioning
confidence: 99%
“…Jones et al [5] indicated that in principle the presence of surfactants in multi-purpose solutions together with rubbing/rinsing steps are likely to be effective against SARS-CoV-2 but further work in this area is required. While a recent review suggested (with no cited evidence) that no rubbing/rinsing is required prior to lens disinfection when using hydrogen peroxide solutions [19], the cleanliness (which is linked to comfort and risk of infection) of RGP and soft lenses soaked in multi-purpose or hydrogen peroxide solution is better after rubbing and rinsing [20][21][22][23]. The survey data showed that 55% of the respondents rubbed their lenses prior to soaking with hydrogen peroxide solution.…”
Section: J O U R N a L P R E -P R O O F Discussionmentioning
confidence: 99%
“…The varying chemicals in MPS work to provide different essential steps in successful rigid corneal lens wear, and the contents of these care systems continue to be regularly updated and improved by manufacturers to provide convenience and efficient disinfection, leading to a wide range of formulations available for contact lens wearers. It is advised that patients receive thorough training in contact lens care, with emphasis on the importance of daily rubbing and rinsing to remove stubborn lens deposits [172]. They should also be cautioned about the cytotoxicity of some MPS constituents, such as chlorohexidine gluconate, which may not be advisable to apply directly to the cornea [171].…”
Section: Multipurpose Solutionsmentioning
confidence: 99%
“…Hydrogen peroxide has also shown good efficacy against lens case-based biofilm formation for bacteria [190,191]. Overall, peroxide-based systems can be a good choice for ortho-k patients [192], particularly those who present with sensitivities to components within MPS, although a rubbing step with a daily cleaner, and rinsing with saline is still recommended as part of the care regime [172].…”
Section: Oxidative Systemsmentioning
confidence: 99%